Effect of Hydrolysis on Tannin and Carotenoid Contents, and Antioxidant Activity of Pouteria campechiana - Hien Xuan Tran; Huong Lien Huynh; Thanh Trung Nguyen (Universitas Andalas, 2020)
The medicinal properties of Pouteria campechiana fruit in Vietnam currently have not been studied much. This study was conducted to evaluate hydrolysis's effect on the carotenoid, tannin, and antioxidant activity through the correlation between IC50 and TPC values of Pouteria campechiana extract. This study examined hydrolysis conditions, such as enzyme type, enzyme concentration, temperature, and hydrolysis time. Experimental results showed that at pectinase enzyme concentration of 0.6 wt%, cellulase enzyme concentration of 0.6 wt%, at hydrolysis temperature of 600C, and 65 minutes for hydrolysis, the study found carotenoid of 115.14±4.14 (µg/g) and tannin of 45.88±2.37 (mgTAE/g)in the extract. IC50 value (7.82±0.21 mg/mL) and TPC content were highly correlated (R2=0.98). This study's results contributed to the provision of valuable scientific data on Pouteria campechiana fruit, especially for the food industry